SUBSTITUTION OF SYNTHETIC HORMONES WITH ORGANIC MATERIALS ON THE GROWTH OF ORCHID PLANTS (Phalaenopsis amabilis) AS A GROWTH REGULATORY SUBSTANCE IN VITRO - Febriana Dwi Wahyuni; Kevin Febrianus Moda; Dimas Ridho Irvansah; Novita Sari (BIOEDUKASI, 2021)
In Indonesia, the agribusiness sector has begun to expand due to the increase in entrepreneurship of orchid plants. Several genera and species of orchid plants are promising to be traded as ornamental plants, one of which is the moon orchid (Phalaenopsis amabilis). However, the limited number of seeds or plants produced by conventional propagation methods takes a long time to get new tillers. Therefore, tissue culture techniques can be used to grow and reproduce moon orchid plants. In the success of in vitro culture, the balance of growth regulators is an essential factor. On the other hand, synthetic hormones such as 1-naphthalenaecetic acid (NAA) and 6-benzylaminopurine (BAP) are relatively expensive. The study in this research is to substitute the synthetic hormones NAA and BAP with organic ingredients that are cheap and easy to find. Such as Purple Sweet Potatoes and Beans and find out the right concentration of organic matter. This study used a completely randomized design with two factorials (concentration of purple sweet potato and green beans) with three repetitions. PLB (Protocorm Like Bodies) moon orchid (Phalaenopsis amabilis) was treated with: positive control (2 ppm), negative control (without the addition of organic or synthetic hormones), and variations in the concentration of purple sweet potato and green beans organic matter. The result was that C4D0 (500g/L purple sweet potato extract and 0 g/L green bean extract) was an excellent formulation, although there was no significant interaction between purple sweet potato and green bean extracts against moon orchid.